2008
DOI: 10.1159/000143499
|View full text |Cite
|
Sign up to set email alerts
|

Schnitzler’s Syndrome: Monoclonal Gammopathy Associated with Chronic Urticaria

Abstract: Schnitzler’s syndrome (SS) is defined by monoclonal gammopathy and chronic urticaria combined with at least two of the following features: fever, arthralgia or arthritis, bone pain, hepato- and/or splenomegaly, palpable lymph nodes, elevated ESR, and leukocytosis. We report a 49-year-old man with monoclonal IgM gammopathy and a 4-year history of recurrent urticarial rash, unexplained fever and arthralgias. The skin biopsy from an acute lesion revealed perivascular lymphocytic infiltrates consisting of CD4+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Purified monoclonal paraprotein from 5 SCLS patients failed to bind cultured endothelial cells or induce any cytotoxicity (12, 52–53). Although the amount of monoclonal Ig produced in MGUS is usually small, indicating few clonal plasma cells, it may produce a toxic monoclonal paraprotein that causes pathology either by aggregating and depositing in tissue, such as in light chain amyloidosis, or by binding to autologous common antigens (i.e., acting as an autoantibody) as in cold agglutinin disease, mixed cryoglobulinemia, vonWillebrand syndrome, paraproteinemic neuropathy, and Schnitzler syndrome (54-57). …”
Section: Cause and Pathophysiologymentioning
confidence: 99%
“…Purified monoclonal paraprotein from 5 SCLS patients failed to bind cultured endothelial cells or induce any cytotoxicity (12, 52–53). Although the amount of monoclonal Ig produced in MGUS is usually small, indicating few clonal plasma cells, it may produce a toxic monoclonal paraprotein that causes pathology either by aggregating and depositing in tissue, such as in light chain amyloidosis, or by binding to autologous common antigens (i.e., acting as an autoantibody) as in cold agglutinin disease, mixed cryoglobulinemia, vonWillebrand syndrome, paraproteinemic neuropathy, and Schnitzler syndrome (54-57). …”
Section: Cause and Pathophysiologymentioning
confidence: 99%
“…26 Most of these patients present with gammopathy and hematologic disorder in their 40s to 60s after 4 to 9 years of chronic urticaria. [27][28][29] To our knowledge, no previous studies have examined the effect of age at onset of chronic urticaria on cancer occurrence. Our study demonstrated that younger patients (aged Ͻ40 years) tend to have the greatest risk of cancer development, especially for hematologic cancers.…”
Section: Commentmentioning
confidence: 99%
“…133 Schnitzler syndrome usually has a benign course and patients show no increased mortality during the follow-up periods, but there is a 10-year 15% risk of developing a lymphoproliferative disorder, most notably Waldenström macroglobulinemia. 133,134 Skin manifestations of Schnitzler syndrome include persistent urticarial lesions, frequently with figurate lesions, leaving a brown hyperpigmentation. Histologic examination reveals a perivascular mixed inflammatory infiltrate with leukocytoclasis, nuclear dust without fibrinoid necrosis, and extravasated red blood cells.…”
Section: Hematologic Diseasesmentioning
confidence: 99%